Analisis Hukum terhadap Praktik Rangkap Jabatan pada Badan Pengelola Investasi Daya Anaganta Nusantara (Danantara) dalam Perspektif Prinsip Good Corporate Governance Berdasarkan Peraturan Pemerintah Nomor 10 Tahun 2025 - Wong, Felicia Maharani; Tiopan , Demson (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The establishment and existence of Danantara as a state investment management institution is grounded in the provisions of Law Number 1 of 2025 and Government Regulation Number 10 of 2025, representing the government’s effort to realize a more centralized and professional governance of state investments. However, the practice of multiple office holdings involving several strategic officials within Danantara raises legal concerns, particularly regarding potential conflicts of interest and the effectiveness of implementing the principles of Good Corporate Governance (GCG). The emerging legal issues focus on the compatibility of such practices with the principles of independence and accountability, which serve as core pillars of GCG in the management of state assets. This study adopts a normative juridical approach supported by statutory and conceptual approaches. The analysis is conducted qualitatively and descriptively based on the provisions contained in Government Regulation Number 10 of 2025, Law Number 1 of 2025, and PER-2/MBU/03/2023. The findings indicate that multiple office holdings within Danantara create overlapping authorities and potential conflicts of interest, thereby rendering them inconsistent with the principles of independence and accountability under GCG.Based on these findings, it can be concluded that the practice of multiple office holdings in Danantara has the potential to hinder the optimal implementation of GCG principles. Therefore, there is a need for strengthened implementing regulations, explicit prohibitions on multiple office holdings, and the development of more comprehensive operational guidelines to ensure that state investment governance is carried out professionally, transparently, and free from conflicts of interest.